Evaluating the effect of allelopathic stress of Silybum marianum Gaertn (L.) and Malva sylvestris L. on the cress (Lepidium sativum L.) sensitive to allelochemicals in order to reduce environmental pollution - Ebrahim Gholamalipour Alamdari; Meisam Habibi; Hematollah Pirdashti; Maral Babayani; Shirin Shoja (رویکردهای نوین در مهندسی آب و محیط زیست)
Experiments were conduccted to study the response of cress (Lepidium sativum) sensitive plant to allelochemical compounds to aqueous extract obtained from the different organs of important weeds such as Silybum marianum and Malva sylvestris. Experiment for each plant was performed as factorial based on the completely randomized design with three replications in 2023. The first factor was the different organs in three levels, namely root, stem, and leaf of weeds, and the different concentrations of the extracts obtained from each of the organs were at 5 levels (0 (control), 25, 50, 75 and 100%) as the second factor. To extract the samples, after collecting and drying them, first 5 g of the plant powder of each organ (weight) was extracted separately with 100 ml of distilled water as solvent (volume). Then different concentrations were prepared from the extract obtained from the stock (base solution). The results showed that the percentage and rate of germination, length of radicle and, plumule, length of seedling, ratio of radicle to plumule, seed length vigor index, dry weight of radicle and, plumule, seedling dry weight and seed weight vigor index of cress were influenced by aqueous extract of the Silybum marianum organs, different concentrations and interaction effect of them. Among the different organs, the aqoues extracts of leaf had the highest inhibitory effect on germination characteristics of cress. So that the difference in the effect of different concentrations of organs was dependent on their concentration threshold. As the findings showed that the effect of aqueous